Leadership and Capacity Building; The Construction of Madrasah Quality Improvement - Dian, Dian; Faizal, Irawan; Hasanah, N. Dewi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to understand the construction of madrasah quality improvement through a leadership system in building human resource capacity building in one Madrasah Tsanawiyah in Bandung Regency. The researcher tries to understand the meaning behind school quality assurance activities by using a case study qualitative approach. Researchers conducted interviews, observations, and documentation to obtain accurate and valid information related to the research theme. Collecting, reducing, presenting data, and drawing conclusions are carried out in data analysis. The research results show that the construction of improving the quality of madrasas through a leadership system in building human resource capacity building in one Madrasah Tsanawiyah in Bandung Regency is carried out through policy analysis organizational commitment, management support system, workforce development, and continuous innovation improvement. This research has implications for the importance of leadership and capacity building that must be adequately managed to increase the competence and skills of existing personnel, thus giving birth to commitment, loyalty, and good performance quality.